PENGARUH SOSIALISASI PERPAJAKAN, PEMAHAMAN, KEMUDAHAN DAN MANFAAT YANG DIRASAKAN WAJIB PAJAK UMKM TERHADAP KEPATUHAN MEMILIKI NPWP (Study Pada Wajib Pajak UMKM di Kota Bengkulu) - Dilla Kurniasi; Halimatusyadiah Halimatusyadiah (UNIB Press, 2018)
The objective of this research is to prove the influence of the socialization of taxation, understanding of taxation, convenience of taxation and benefits that were felt by UMKM taxpayers against compliance to have NPWP. Data used in this research are primary data that were obtained from questionnaires that distributed to taxpayers. The number of questionnaires distributed were 155 questionnaires, but only 93 questionnaires that could be processed. Data were analyzed by multiple linear regression that using SPSS program. The result of this research showed that the socialization of taxation, understanding of taxation, convenience of taxation and benefits of taxation have positive influence and significant against taxpayers compliance to have NPWP. This research can contribute to KPP Pratama Bengkulu City to increase tax revenue target by collecting taxpayers to have a tax identification number (NPWP). The limitation of this research are on the number of questionnaires that distributed only in several sub-district in Bengkulu City. Therefore, further research is suggested to expand the research areas.Key words: Socialization, Understanding, Taxation, Benefit, Compliance.